Schematic Description of the Monetary Dispute - Seminario Dapello, Arturo (1972)
This paper addresses the monetary controversies linked to the potential change of gold as a financial asset and the implications of adopting a new system comprising a different unit of value. In this sense, the author analyzes the influence of the United States on monetary policy and the changes in the monetary system based on the positioning of other economies in the international community. Since gold plays a predominant role in the monetary system, the absence of this element would have as a consequence the redefinition of other currencies, since they found in gold a common binding value. Likewise, the author states that monetary systems reflect a political and economic reality and the geographical structure of international trade; therefore, the repercussions of changes in international reserves, external debt, prices and employment must be taken into consideration.